Optimization of discus flight - Schüler, A.; Hildebrand, F.; Waldmann, J. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
We use a 3-D model for men`s and women`s discus flight including initial discus flight path angle, angle of attack, pitch attitude as well as release speed v0 and initial spin rate p0. We study in detail optimal release conditions depending on a constant wind velocity of v0 =5 m/s blowing from different directions ?=0°, 10° up to 350°. Here ? =0°, 180°, 90°, and 270° correspond to tail wind, head wind, wind from the left, and wind from the right, respectively. The optimal wind for men is head wind from the right (?= 220°). In this case optimal men`s strategy at v0=25 m/s is ?0 = 33°, ?0= 23°, ?0= 30° with a range r=74.80 m. Optimal wind for women is wind exactly from the right (?= 270°). The optimal women`s strategy at v0=24 m/s is ?0 = 41°, ?0= 32°, ?0 = 30° with a range r=61.26 m. In all cases we assume an initial spin rate of p0=50 rad/s. At the moment of release, the angle of attack of the discus symmetry plane should always be less than the flight path angle. Also, we can show that a faster-spinning discus imparts greater gyroscopic stability and therefore achieves a better throw. We used evolutionary algorithms to perform the optimization.